A pilot study monitoring the thermal comfort of the elderly living in nursing homes in Hefei, China, using wireless sensor networks, site measurements and a survey. Issue 3 (March 2020) - Yu, Jingyu; Hassan, MD Tanbir; Bai, Yongzhen; An, Ning; Tam, Vivian W. Y.
Due to the rapid growth of the ageing population and the shrinking of family size in China, there has been a steady increase in the demand for nursing homes. The Chinese government has encouraged the development of nursing homes. However, there is no clear understanding of the thermal environment of nursing homes and the thermal comfort of their residents. Therefore, this paper describes a pilot study that was undertaken to investigate the thermal comfort of senior residents living in nursing homes. A wireless sensor network system was developed to continuously monitor the thermal environment of nursing homes for an entire year. Site measurements and a questionnaire also were conducted. The results revealed significant seasonal variations in the thermal environment of nursing homes and in the thermal comfort, thermal sensation and adaptive behaviours of older adults. The calculation of thermal comfort was modified according to the older adults' behaviour patterns. The knowledge acquired in this initial study will enrich knowledge of the thermal comfort of older adults living in nursing homes. It also will provide preliminary insights for caregivers, designers and policymakers in their efforts to deliver a more comfortable, healthy and sustainable environment in nursing homes in China.